2022
DOI: 10.1088/2051-672x/ac5c68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laser texturing pre-treatment on HVOF-sprayed WC-10Co-4Cr+GNP coatings on AISI 304

Abstract: High-Velocity Oxygen Fuel (HVOF) is one of the most important thermal spraying techniques for protective coating on pristine alloy surfaces by cermet feedstock powders. In the article, grit blasting before HVOF coating is replaced by laser texturing to create specific roughness and deterministic cavities pattern for better mechanical interlocking of deposited WC-10Co-4Cr + 3% Graphene Nanoplatelets (GNPs) on AISI 304 Steel Substrate. Two geometries; first one is Circular texturing (CT) of diameter (d) 100 μm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Water contact angles (WCA) observed for specimens 1, 2, 3 and 4, was 63.5°, 57.7°, 45°, and 64°respectively. Important factors affecting the wettability of a surface, are surface energy, surface roughness, and the presence of microstructural attributes [26,27]. Test results confirmed that by adding HEA to titanium increased wettability was observed.…”
Section: Wettabilitymentioning
confidence: 67%
“…Water contact angles (WCA) observed for specimens 1, 2, 3 and 4, was 63.5°, 57.7°, 45°, and 64°respectively. Important factors affecting the wettability of a surface, are surface energy, surface roughness, and the presence of microstructural attributes [26,27]. Test results confirmed that by adding HEA to titanium increased wettability was observed.…”
Section: Wettabilitymentioning
confidence: 67%
“…The influence of LST as pre-processing of AISI 304 for coating was characterized by surface roughness, wear test, and scratch test. During the wear test, few microcracks were observed for high load values, and a reduced wear rate was confirmed [39]. LST could be the crucial parameter to contribute complete diffusion between the interlayer and the joining materials as it provides surface modification.…”
Section: Laser Surface Texturingmentioning
confidence: 76%
“…Kumar et al [6] in their recent work have proposed the addition of GNPs in WC-10Co-4Cr coating powder to improve the wear behaviour of AISI 304 steel substrate. After pin-on-disc and micro-scratch testing, it was observed that wear-resistance of the coated surface improved significantly as compared to bare steel substrate due to lubrication nature of GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that graphene possesses a twodimensional carbon honeycomb lattice with a single layer and the coating of such micro-structure is helpful to reduce co-efficient of friction and wear of the surface [7]. HVOF is an apt coating technique among the existing methods for applying the combination of WC-10Co-4Cr+GNP feedstock powder due to resultantly increased surface wear-resistance, greatest bond strength, and minimum porosity caused by high impact velocity [6,8,9]. In the HVOF approach, shorter in-flight exposure time and higher velocities reduce oxide formation and produce a smoother assprayed surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation